Plasma Levels and Therapeutic Effect of 25-Hydroxycholecalciferol in Epileptic Patients taking Anticonvulsant Drugs. Issue 5831 (7th October 1972) - Stamp, T. C. B.; Round, J. M.; Rowe, D. J. F.; Haddad, J. G.
Abstract : Plasma levels of 25-hydroxycholecalciferol (25-HCC) were measured by a specific competitive protein-binding assay. Mean levels in both normal London adults and adolescent schoolchildren were 16 ng/ml and the mean level in a group of epileptic patients on high-dosage anticonvulsant therapy was 5 ng/ml, (difference from normals P < 0·001). Two further epileptic patients, with well-marked anticonvulsant osteomalacia, were treated with small doses of 25-HCC during full metabolic balance studies; rapid healing followed administration of 25-HCC by mouth in doses of 10-45 μg daily, which is well below the effective dose range of calciferol in this condition. These findings provided further evidence that anticonvulsant osteomalacia results from hepatic enzyme induction which, by increasing the metabolism of cholecalciferol to inactive compounds, lowers 25-HCC levels in patients whose dietary vitamin D intake and exposure to sunlight are otherwise adequate. Results also indicated that under certain circumstances 25-HCC may have considerably stronger antirachitic potency in man than has hitherto been recognized.